The Development Pattern of The Gowa-Maros New City as an Edge City Based on GIS (Geographic Information System) - Virda Evi Yanti Deril (Jurnal Info Sains : Informatika dan Sains, 2023)
The development of the new city of Gowa-Maros is one way to address the inability of th core city (Makassar City) to support the impact of urbanization  experienced by the current Metropolitan Mamminisata. This study aims to identify the development trend of Gowa- Maros New Town as an edge city that impact on the sustainability of Metropolitan Mamminasata urbanization. This research includes descriptive research type using quantitative data. Characteristic of new town developments in this study focuses on the physical, social and demographic, and economic aspects of the region with references to the edge city indocators. Furthermore, related to the development impact of Gowa-Maros New Town, efforts to reduce the burden of the core city (Makassar City) in support of Metropolitan Mamminasata urbanization is identified based on the characteristics of the current development of the region. The result of this study indicate that the tendency of the Gowa-Maros New Town suitability with further edge city indicators has a positive direct impact on metropolitan development, particularly with regard to regional structure, increased employment opportunities, and regional economic structure growth.